1981
DOI: 10.1007/bf01420003
|View full text |Cite
|
Sign up to set email alerts
|

Natural radiative lifetimes in the perturbed 6snd 1 D 2 sequence of barium

Abstract: Natural radiative lifetimes in the perturbed 6sns ~D 2 (n= 12-30) sequence of barium have been measured using the PUMOLS (PUlse-MOdulated Laser Spectroscopy) method, which incorporates pulse-modulation of a CW dye-laser beam and delayed coincidence techniques. Principal perturbers are the 5d 7d 3F 2 and ~D 2 states. Lifetimes were also measured for these shortlived valence states, which through configuration mixing cause drastic decreases in lifetime values in the region of perturbation of the 6snd 1D z sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Similar perturbations are observed in many different situations like in the alkaline-earth atoms where perturbations of Rydberg series by isolated levels considerably modify the lifetime values (see, e.g. Bhatia et al (1981) and Aymar et al (1982)). Baylis (1979a, 1979b) have demonstrated that correlation effects between valence and core electrons can be approximated by core-polarization corrections in relativistic single-configuration Hartree-Fock computations of oscillator strengths.…”
Section: Introductionsupporting
confidence: 69%
“…Similar perturbations are observed in many different situations like in the alkaline-earth atoms where perturbations of Rydberg series by isolated levels considerably modify the lifetime values (see, e.g. Bhatia et al (1981) and Aymar et al (1982)). Baylis (1979a, 1979b) have demonstrated that correlation effects between valence and core electrons can be approximated by core-polarization corrections in relativistic single-configuration Hartree-Fock computations of oscillator strengths.…”
Section: Introductionsupporting
confidence: 69%
“…j Reference [21]. k Reference [15]. l Affected by strong cancellation effects that lengthen the calculated lifetime.…”
Section: Theoretical Determination Of Lifetimesmentioning
confidence: 99%
“…Experimental measurements of radiative lifetimes for some even-parity levels [13][14][15][16][17][18][19][20][21] and calculations for the 6snf 3 F 2 (11 n 35) Rydberg series and some 6s6p, 6s7p, 5d5p, and 5d6p levels [22,23] have been reported. But because it is difficult or impossible to excite most of the high-lying odd-parity levels from the ground level 1 S 0 and because the lowest metastable levels 6s5d 3 D J (J = 1 to 3) located above 9000 cm −1 are difficult to populate in a thermal atomic beam, direct lifetime measurements for such levels are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In particu-tar, the wavefunctions of the 6s 14d 1, 3Dz and 5d7d 3k~ level have to be tested for ability to describe lifetime [5] and hyperfine-structure data [11]. In fact it is very difficult for MQDT to well parametrize the localized perturbation occuring in energy ranges, where Rydberg levels are widely separated and the new wavefunctions obtained for the 6s 14d 1,3D2 level, although consistent with gj measurement, are certainly less reliable than wavefunctions for high-lying levels.…”
Section: Resultsmentioning
confidence: 99%
“…It is of considerable interest to test to what extent MQDT wavefunctions can be used for reliable prediction of various quantities. Recently, three independent investigations of natural lifetimes in the perturbed 6snd I'3D z sequences of Ba were performed [5][6][7]. Close to the perturbing Ba 5 d 7 d 3F2, and especially the 5 d 7 d 1D 2 state, strong resonant changes in the measured lifetimes are observed.…”
Section: Introductionmentioning
confidence: 94%